The parchment of Kashmir history, society, and polity - Khan, Nyla Ali 1972- (Palgrave Macmillan, 2012)
"In this volume, Kashmiri scholars of all disciplines undertake a new look at their homeland and provide a set of visions for Kashmiri culture and society. The book offers a panorama of key cultural concerns of Jammu & Kashmir today, from the military aspects of the Kashmir conflict to the modern-day revival of indigenous cultural institutions, from the effects of religious discourse and gender-based social hierarchy to relations with India and Pakistan"--Provided by publisher